P-668 The LH endocrine profile in Gonadotropin-Releasing Hormone analogue cycles. (30th June 2022) - Janssens, L; De Neubourg, D; Roelant, E
Abstract: Study question: What does the evolution of luteinizing hormone (LH) throughout the follicular phase look like in different treatment protocols for ovarian stimulation in IVF/ICSI? Summary answer: Evolution of LH during the follicular phase of ovarian stimulation differs between Gonadotropin-Releasing Hormone (GnRH) analogues, with a significant decrease of LH in antagonist cycles. What is known already: Physicians aim to tailor ovarian stimulation protocols to the patient, with protocols varying in type of GnRH analogue and gonadotropin. However, there is no clear consensus on the best treatment protocol and especially the role of LH is still not completely understood as earlier studies focused mainly on suppressing LH levels. Literature has since indicated that excessively suppressed LH levels could be detrimental for clinical outcomes. Research on LH is hampered by multiple measurements during the cycle, different treatment schedules and patients switching schedules over time. Study design, size, duration: This was a non-interventional, retrospective, observational cohort study. 2200 ovarian stimulation cycles for assisted reproduction were analyzed, in 1303 individual patients. Patients were treated during the period of January 1 st 2015 until September 30 th 2020. Cycles were included if the patient was between 18 and 43 years of age, stimulated with human menopausal gonadotropin (hMG) or recombinant follicle stimulating hormone (rec-FSH, follitropin α or β) and using GnRH analogues. Participants/materials, setting, methods: Data were extracted from two databases used at a tertiary infertility clinic. Cycles were divided into six treatment protocols: GnRH antagonist/hMG (13.8%), antagonist/rec-FSH (19.7%), long agonist/hMG (35.7%), long agonist/rec-FSH (4.8%), short agonist/hMG (22.5%) and short agonist/rec-FSH (3.5%). 59.5% of cycles were pretreated with an oral contraceptive pill (OCP). LH evolution was visualized by plotting LH levels against the days of the follicular phase and repeated daily LH measures were fitted with a linear mixed model. Main results and the role of chance: Basal LH was significantly lower in antagonist/hMG cycles pretreated with OCP compared to no pretreatment (estimated difference -1.23 IU/L, p < 0.001). Mean LH value throughout the follicular phase was significantly lower with OCP pretreatment in antagonist/hMG (estimated difference -1.05 IU/L, p < 0.001) and antagonist/rec-FSH cycles (estimated difference -0.52 IU/L, p < 0.001). When LH evolution throughout the follicular phase was analyzed, no significantly different evolution between cycles with and without OCP was detected (all p > 0.1). Hence further analysis of the LH profiles was performed in the six protocol groups making no distinction between OCP use or not. LH evolution was significantly different between all six protocol groups (p < 0.001). In antagonist/hMG cycles, LH values showed a significant decrease of 0.17 IU/L per day (p < 0.001). In antagonist/rec-FSH cycles, the decrease per day was 0.26 IU/L (p < 0.001).The decrease in LH was significantly larger in rec-FSH cycles than hMG (estimated difference 0.09 IU/L per day, p < 0.001). Short agonist/hMG cycles showed a significant increase in LH of 0.04 IU/L per day (p = 0.002), while the increase of 0.01 IU/L per day in rec-FSH cycles was not significant (p = 1.00). In long agonist cycles, no significant in- or decrease in LH values during the follicular phase was found (p = 1.00). Limitations, reasons for caution: Stimulation protocols were chosen by the treating physician which is a limitation of the retrospective design. The authors were able to partly respond to this limitation by adjusting for age and using different cycles per patient in all mixed models. Wider implications of the findings: Using profiles to show LH evolution allowed the visualization of the decrease in the evolution of LH in antagonist cycles, even more pronounced in cycles stimulated with rec-FSH compared to hMG. This decrease in LH and the potential impact on estradiol levels and follicle growth needs further examination. Trial registration number: not applicable